Characterization of ultrasonic pulse in reinforced concrete as the corrosion of reinforcing bars progresses with time - Mesias, Vince Gerard S.
Corrosion of steel reinforcements in a structure is a condition that normally happens through its lifespan. It can lead to cracking, spalling and delamination of the concrete cover. Non-destructive tests are now used in the assessment of the structure. The research project aims to characterize the wave generated by the ultrasonic pulse with respect to time by the simulation of corrosion of reinforcing bars on the reinforced concrete through accelerated corrosion test. Specimens were generated with a fix water-to-cement ratio of 0.5 that was usually used in the construction of public buildings. The generated specimens were characterized with the aid of the ultrasonic method. The characterization of wave generated considered the effects of the varying parameter such as the comparison between the mortar specimens from the reinforced concrete specimens; the comparison between the new reinforcing steel bars and initially corroded reinforcing steel bars; and the corresponding degree of corrosion of the reinforcing steel bars. Results showed that the attenuation of the ultrasonic wave due to the corrosion of reinforcing bars decreased with respect to corrosion time. Also, the dominant frequency decreased in the region with the presence of reinforcing bars. It was also observed that the mass loss due to corrosion accelerated through time.